An innovative ski-boot: Design, numerical simulations and testing - Corazza, S.; Cobelli, C. (Journal of Sports Science & Medicine, 2005)
The present work is concerned with the design of an innovative ski-boot. In order to optimize ergonomics and biomechanical behavior of the ski-boot it is important to take into account the orientation of the leg with respect to the ground. The SGS system (Stance Geometry System) developed in this work allows the skier to adjust for posture in the frontal plane by rotating the sole of the boot about the anteroposterior axis (ski-boot is then locked in the desired position before skiing). A simplified model of the effect of ski-boot deformation on skiing behavior is used to evaluate the minimal stiffness the system must have. An experimental analysis on the ski slopes was carried out to provide ski-boot deformations and loading data in different skiing conditions, to be used in numerical simulations. Finite Elements Method (FEM) simulations were performed for optimal design of the joint between ski-boot and sole. The active loads and local ski-boot deformations during small- and large-radius turns were experimentally determined and used to validate a FEM model of the ski-boot. The model was used to optimize the design for maximum stiffness and to demonstrate the efficacy of virtual design supported by proper experimental data. Mean loads up to 164% body weight were measured on the outer ski during turning. The new SGS design system allows the adjustment of lateral stance before using the ski-boot, optimizing the ski-boot stiffness through FEM analysis. Innovative aspects of this work included not only the stance geometry system ski-boot but also the setup of a virtual design environment that was validated by experimental evidence. An entire dataset describing loads during skiing has been obtained. The optimized SGS ski-boot increases intrinsic knee stability due to proper adjustment of lateral stance, guaranteeing appropriate stiffness of the ski-boot system.